Analyzing the reliability of Chinese outward FDI studies: a replication approach. Issue 4 (5th October 2020) - Anderson, John; Sutherland, Dylan; Zhang, Fan; Zan, Yangyang
Abstract : Purpose: Many academic studies in international business empirically test the determinants of Chinese outward (O)FDI. A weakness with these studies is the limited critical evaluation given to the way in which Chinese OFDI data is collected and used. Chinese multinational enterprises (C)MNEs frequently establish special purpose entities in tax havens to transit FDI via intermediary jurisdictions. The purpose of this paper is to develop an alternative approach for measuring CMNE OFDI and subsequently explore how the results of previous studies may have been confounded use of tax havens by MNEs. The authors address the latter question by replicating widely cited quantitative studies. Design/methodology/approach: Replication approach. Findings: Through the replication of several studies, this paper finds high levels of discrepancies in general sign and significance between global ultimate ownership modeling results and those using officially recorded FDI data. More specifically, the main areas impacted by using official data rather than data which accounts for the use of tax havens are cultural proximity, geographic distance and natural resource seeking. Practical implications: This paper looks at studies, which use official FDI data to understand CMNE behavior. It is important to note, however, that there are many hundreds, if not thousands, of studies that use other national-level FDI data to draw similar types of inferences about MNE activity. In this sense, the authors' critical evaluation of CMNE work holds a much broader and, arguably, more important question: How reliable, in general, are studies, which use officially recorded FDI data? The results from this paper have already caused reflection on the impact of tax haven use on official FDI collection organizations, such as the OECD. Social implications: The social implications of companies using tax havens to route FDI is immense. The use of tax havens not only aids in tax minimization for companies, but also obscures the true providence and identity of companies. This is problematic in a society, which increasingly desires to understand where, how and by whom a product or service was created prior to consumption. Originality/value: This paper argues that the tendency for Chinese MNEs to establish offshore holding companies in tax havens has given rise to significant biases in official FDI statistics. Through the use of global ultimate ownership data, the authors have put forward an alternate approach to measure genuine CMNEs' OFDI activity, one which confronts and deals with their pervasive engagement with tax havens. Through the replication of several Chinese OFDI location choice studies, it was possible to understand how methodological issues stemming from the use of official FDI data may influence prior econometric results. In doing so, the authors hope to have sparked a debate which may lead to a re-evaluation of earlier received wisdom regarding Chinese MNE investment strategy and behaviors. This in turn should foster improved theorizing regarding the Chinese MNE and its outward investment activities.